Does economic growth, international trade and urbanization uphold environmental sustainability in sub-Saharan Africa? Insights from quantile and causality procedures - Chimere Okechukwu Iheonu; Ogochukwu C. Anyanwu; Obinna K. Odo; Solomon Prince Nathaniel (African Governance and Development Institute (AGDI), 2021)
International trade and urbanization are increasing at an unprecedented rate in sub-Saharan Africa (SSA). The region has also witnessed a fair share of economic growth, with minimal investment and consumption of renewables. Therefore, this study investigates the influence of economic growth, international trade, and urbanization on CO2 emissions in SSA. The current study enriches the existing literature by employing the panel quantile regression analysis to account for existing levels of CO2 emissions in the region. Empirical findings reveal that GDP increases CO2 emissions across quantiles, especially in countries where the existing level of CO2 emissions is low. International trade improves environmental sustainability in countries where the existing levels of CO2 emissions are at their lowest and highest levels but exacts a reversed impact on CO2 emissions at the median. Further findings suggest that urbanization increases CO2 emissions across the observed quantiles with a more pronounced effect in countries where the existing levels of CO2 emissions are at its lowest level. The study also reveals a bi-directional causality between economic growth, international trade, urbanization, and the emissions of CO2. The limitations of the study and possible direction for future research have been highlighted. Policy directions are discussed.
Keywords: 330; Economic Growth; International Trade; Urbanization; CO2 Emission; sub-Saharan Africa; Quantile Regression